Plant community responses to experimental climate manipulation in a Welsh ombrotrophic peatland and their palaeoenvironmental context. (9th December 2021) - Andrews, Luke O.; Rowson, James G.; Caporn, Simon J. M.; Dise, Nancy B.; Barton, Eleanor; Garrett, Ed; Gehrels, W. Roland; Gehrels, Maria; Kay, Martin; Payne, Richard J.
Abstract: We test whether vegetation community composition from a 10‐year climate manipulation experiment on a Welsh peat bog resembles vegetation communities during periods of climate change inferred from a peat core. Experimentally warmed and combined warmed and droughted treatments drove significant increases in ericaceous shrubs but Sphagnum was unaffected. Similarly, Calluna vulgaris seeds increase during inferred warmer periods in the palaeoecological record. Experimental short‐term episodic drought (four 4‐week drought treatments) did not affect vegetation. Plant community composition has undergone several abrupt changes throughout the past c. 1500 years, often in response to human disturbance. Only slight changes occurred during the Medieval Climate Anomaly (c. 950–1250 Common Era [CE]) in vegetation and hydrology, while abrupt changes occurred during the Little Ice Age (c. 1300–1850 CE) when water tables were highest, suggesting that these shifts were driven by changes in water table, modulated by climate. A period of water table drawdown c. 1800, synchronous with historical records of increased drainage, corresponds with the development of the present‐day vegetation community. Modern analogues for fossil material, characterized by abundant Rhynchospora alba and Sphagnum pulchrum, are more common after this event. Vegetation changes due to climate inferred from the palaeo record differ from those observed in the experiments, possibly relating to differences in the importance of drivers of vegetation change over varying timescales. Whereas temperature is frequently identified as the dominant driver of plant community change in experiments, sustained changes in water table appear to be more important in the long‐term record. We find evidence that recent climate change and other anthropogenic stressors (e.g. drainage, heavy metal and nitrogen pollution) may promote the development of novel plant communities without analogues in the fossil record. These communities may be poorer at sequestering carbon and may respond differently to future climate change. Abstract : We compared vegetation responses to experimental warming and drought over 10 years in a Welsh raised bog with a 1500‐year record of vegetation change from the same site. Shrub‐type vegetation became more abundant with warming in the experiment, which was also reflected in the long‐term record during warmer periods. Sphagnum abundance was unaffected, and increased drought frequency also had no effect upon vegetation. In the long‐term record, human activity (burning and drainage) resulted in abrupt changes in vegetation. We find that the modern‐day vegetation composition of the site are not analogous with communities that existed throughout much of the past. Crynodeb: Rydym yn aprofi os mae cyfansoddiad cymuned planhigion mewn arbrawf trin hinsawdd o 10 mlynedd ar gors mawn yn Gymru yn debyg i gymunedau oedd yn bodoli yn ystod cyfnodau o newid yn yr hinsawdd, e.e., yr Anomaledd Hinsawdd Canoloesol (AHC ‐ c. 950‐1250 CE), a nodwydd o graidd mawn. Fe wnaeth triniaethau arbrofol o cynhesu a cynhesu yn cyfunol efo sychder gyrru cynyddu sylweddol mewn phrysgwydd ericaceous. Doedd na ddim effaith ar digonedd Sphagnum. Yn yr un modd, nath hadau Erica tetralix a Calluna vulgaris cynyddu yn ystod cyfnodau cynhesach a gasglwyd yn y cofnod palaeoecolegol. Ni wnaeth sychder episodig tymor byr arbrofol (pedair triniaeth sychder o 4 wythnos) effeithio cymuned planhigion. Mae cyfansoddiad cymuned planhigion wedi profi sawl newid sydyn trwy gydol y gorffennol c. 1500 flynyddoedd, yn aml mewn ymateb i aflonyddwch dynol. Dim ond newidiadau bach a ddigwyddodd yn ystod yr AHC ar gyfer planhigion a hydroleg, tra digwyddodd newidiadau sydyn yn ystod yr Oes Iâ Fach (tua 1300‐1850 CE) pan oedd y trwythiadau dŵr ar eu uchaf, sydd yn awgrymu bod y newidiadau hyn yn cael eu gyrru gan newidiadau yn y lefel trwythiad, wedi'u modiwleiddio gan yr hinsawdd. O gwmpas c.1800 mae yna cyfnod o dynnu i lawr trwythiad dwr, sy'n gydamserol â chofnodion hanesyddol o ddraeniad cynyddol, yn cyfateb i ddatblygiad y gymuned planhygion heddiw. Mae analogau modern ar gyfer deunydd ffosil, a nodweddir gan Rhyncospora alba a Sphagnum pulchrum, yn fwy cyffredin ar ôl y digwyddiad hwn. Mae newidiadau llystyfiant oherwydd hinsawdd a gwelodd yn yr cofnod palaeo yn wahanol i'r rhai a arsylwyd yn yr arbrofion, o bosibl yn ymwneud â gwahaniaethau ym mhwysigrwydd gyrwyr newid llystyfiant dros amserlenni amrywiol. Tra bod tymheredd yn aml yn cael ei nodi fel prif ysgogydd newid cymunedol planhigion mewn arbrofion, mae'n ymddangos bod newidiadau parhaus yn y lefel trwythiad yn bwysicach yn y tymor hir. Mae yna tystiolaeth y gallai newid yn yr hinsawdd yn ddiweddar, efo phwysleisiau anthropogenig eraill (e.e. draenio, llygredd metel trwm a nitrogen) hyrwyddo datblygiad cymunedau planhigion newydd heb analogau yn y cofnod ffosil. Efallai bod y cymunedau hyn yn dlotach wrth atafaelu carbon a gallant ymateb yn wahanol i newid yn yr hinsawdd yn y dyfodol.